RETELLING STORY THROUGH PICTURE SERIES TO IMPROVE STUDENTS' SPEAKING SKILL - Mulya, Ika Ratna (2014)
This research investigated the use of retelling story through picture series to improve students' speaking skill at the 8th grade students of junior high school. It used a quasi-experimental design. It involved two classes which consist of 40 students in 8th grade of one of junior high schools in Bandung. The data were examined from the test (pre-test and post-test) and assessed by two teachers. The data were analyzed based on the scoring system for speaking by Haris (1969, cited from Rizqon, 2011). Based on the statistical computation of dependent t-test, it showed that retelling story through picture series is effective in improving students' speaking ability (tobt 12.303 >tcrit 2.093, r = 0.518). In conclusion, the method revealed that retelling story through picture series can improve students' speaking skill. In that, it has significant influences to students' speaking activities. Moreover, this research explains that retelling story through picture series built students' confidence. However, it is important for the teacher to help students develop their motivation/to create activities or use pictures to develop students' motivation to get better result. Keywords: retelling story, picture series, speaking. Penelitian ini meneliti mengenai penggunaan menceritakan kembali cerita melalui gambar berseri untuk meningkatkan keterampilan berbicara pada siswa kelas 8 SMP. Penelitian ini menggunakan meode kuasi eksperimental. Penelitian ini melibatkan dua kelas yang terdiri dari 40 siswa kelas 8 SMP di salah satu sekolah di Bandung. Data diperoleh dari hasil test (pre-test dan post-test) serta dinilai oleh dua orang guru. Data dalam penelitian ini dianalisis berdasarka system penilaian untuk berbicara oleh Haris (1969, dikutip dari Rizqon, 2011). Berdasarkan perhitungan statistik dependent t-test, menunjukan bahwa menceritakan kembali cerita melalui gambar berseri sangat effekif dalam meningkatkan kemapuan berbicara siswa (tobt 12.303 > tcrit 2.093, r = 0.518). dalam kesimpulannya, metode ini mengungkapkan bahwa menceritakan kembali cerita cerita melali gambar berseri dapat meningkatkan kemampuan berbicara siswa. Dalam hal ini, hal tersebut memiliki pengaruh yang signifkan terhadap kegiatan berbicara siswa. Selain itu, penelitian ini menjelaskan bahwa menceritakan kembali cerita melalui gambar berseri dapat membangun kepercayaan diri siswa. Namun, sangat penting bagi guru untuk membantu siswa mengembangkan motivasi mereka/membuat kegiatan atau menggunakan gambar untuk mengembangkan motivasi siswa untu mendapatkan hasil yang lebih baik.